Two Successive Inversional Vβ rearrangements on a Single Tcrb Allele Can Contribute to the TCRβ Repertoire - Lee, Kyutae D. (J Immunol, 2019)
Mammalian TCRβ loci contain 30 Vβ gene segments upstream and in the same transcriptional orientation as two DJCβ clusters, and a downstream Vβ (TRBV31) in the opposite orientation. The textbook view is upstream Vβs rearrange only by deletion, and TRBV31 rearranges only by inversion, to create VβDJCβ genes. Here, we show in mice that upstream Vβs recombine through inversion to the DJCβ2 cluster on alleles carrying a pre-assembled Trbv31-DJCβ1 gene. When this gene is in-frame, Trbv5 evades TCRβ-signaled feedback inhibition and recombines by inversion to the DJCβ2 cluster, creating αβ T cells that express assembled Trbv5-DJCβ2 genes. On alleles with an out-of-frame Trbv31-DJCβ1 gene, most upstream Vβs recombine at low levels and promote αβ T cell development, albeit with preferential expansion of Trbv1-DJβ2 rearrangements. Finally, we show wild-type Tcrb alleles produce mature αβ T cells that express upstream Vβ peptides in surface TCRs and carry Trbv31-DJβ2 rearrangements. Our study indicates two successive inversional Vβ-to-DJβ rearrangements on the same allele can contribute to the TCRβ repertoire.